ENGLISH-A STUDY OF RELIGIOUS ORIENTATION AND PERFORMANCE AMONG UNIVERSITY STUDENTS - Asif Iqbal; Zahida Javaid (دی اسکالر)
The role of religion is undeniable in the life of mankind since their existence. It is an acknowledged fact that religious minded people performed better in every walks of life with negligible worries. The study is an attempt to examine the effects of religious orientation on performance students at university level. The students of university of education Faisalabad campus were the population of the study. For this purpose, 309 students were randomly selected form six departments. They were further subdivided from social sciences 123 students and basic sciences 186 students. There were one hundred and eighty-one students belonged to males and one hundred and twenty-eight students belonged to female category. The adapted instrument Religious Orientation Scale [ROS] was used. Data were analyzed using SPSS 24. Pearson r, t-test and ANOVA were applied for the results. The findings of the study showed that university students have strong values of religious orientation. Female students have greater achievement score and religious orientation than that of males. Basic sciences students were found to have greater achievement score than that of social sciences students. There is a strong positive correlation exists among intrinsic, extrinsic and overall religious orientation. It is suggested that in order to promote spiritual well-being through religious orientation, seminars and workshops in higher educational institutions may be conducted.